SYNTHESIS OF COPPER NANOPARTICLES USING ASCORBIC ACID AND CETYL TRIMETHYL AMMONIUM BROMIDE - Singh, Saurabh; Kumar, Bimlesh; Pandey, Narendra Kumar; Kaur, Barinder; Kumar, Arun; Baghel, Dileep Singh; Chauhan, Malti G.; Singh, Sachin Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study highlights the development of a method to synthesize copper nanoparticles (CuNPs). Methods: CuNPs were developed using 0.01 M copper penta sulfate and 0.11 M of ascorbic acid (AA) and 0.03 M of cetyl trimethyl ammonium bromide solution. The synthesized CuNPs were differentiated through filtration and washed by water (deionized). CuNPs were kept in dialysis bag 70 KD in a 250 mL glass beaker along with distilled water. The assembly was kept on a magnetic stirrer for 24 h at 500 rpm. Then, the dialysis bag containing CuNPs solution was filtered by a filter assembly with 0.2 Î¼m nylon filter. The filtered CuNPs were spray dried with the help of spray drier. Results: The prepared CuNPs were found to be 440 nm with zeta potential of âˆ’10 mV and polydispersity index 0.314. Conclusion: The investigation deciphers the promising and material technique to synthesis of CuNPs by methods for synthetic reduction utilizing strategy using AA (0.2 M) and sodium hydroxide (1 M), and Syloid 244FP.